Preparation and characterization of an oridonin and γ-cyclodextrin complex - ZHOU,Wei (2022)
Abstract Oridonin, a terpenoid with various biological functions, has limited uses in the functional food and pharmaceutical industries owing to its low water solubility. Previous studies have used cyclodextrin inclusion to improve its solubility. Herein, the effects of different cyclodextrins on the inclusion of oridonin were investigated using phase solubility and molecular docking tests. The binding constants of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin with oridonin were 22.6, 298.6, and 317.4, respectively. The corresponding binding energies were -6.49, -6.76, and -7.53 kcal/mol, respectively, suggesting that the interaction between γ-cyclodextrin and oridonin was the strongest, thereby improving the solubility of oridonin to the greatest extent. Further experiments indicated that no new unsaturated bonds formed after oridonin complexed with γ-cyclodextrin. In addition, the complexation of oridonin with γ-cyclodextrin, led to its complete dispersal in an amorphous state that was thermally stable. This study promotes the application of oridonin in food and medicines.